2009
DOI: 10.1897/08-485.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic gestagens on fish reproduction

Abstract: Abstract-Although it is well known that estrogenic steroidal hormones are able to affect the sexual development and reproduction of fish at low concentrations, no data on environmental effects of the class of progestogenic hormones are available yet. Synthetic gestagens (progestins) are a component in oral contraceptives. Upon their use, a fraction of the progestins will be excreted via urine into the aquatic environment. On the basis of their pharmacological action in mammals, it is supposed that fish reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
194
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(221 citation statements)
references
References 23 publications
18
194
0
3
Order By: Relevance
“…In agreement with this, strong androgenic effects of LNG were also observed in three-spined sticklebacks (Gasterosteus aculeatus), including the induction of a male specific glue protein, called spiggin, at concentrations ≥40 ng/L, and the disruption of the androgen-dependent reproductive cycle in males at concentrations ≥6.5 ng/L (Svensson et al, 2013(Svensson et al, , 2014. Exposure of fathead minnows (Pimephales promelas) to LNG (29.6 ng/L) resulted in the masculinization of female secondary sex characteristics (Zeilinger et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with this, strong androgenic effects of LNG were also observed in three-spined sticklebacks (Gasterosteus aculeatus), including the induction of a male specific glue protein, called spiggin, at concentrations ≥40 ng/L, and the disruption of the androgen-dependent reproductive cycle in males at concentrations ≥6.5 ng/L (Svensson et al, 2013(Svensson et al, , 2014. Exposure of fathead minnows (Pimephales promelas) to LNG (29.6 ng/L) resulted in the masculinization of female secondary sex characteristics (Zeilinger et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Progestins (also called progestogens) are synthetic pharmaceutical compounds that are commonly used in contraception and hormone replacement therapies (Zeilinger et al, 2009). Similar to estrogens and androgens, progestins can enter the aquatic environment through wastewater treatment plant effluents, and pastoral agricultural runoff (Chang et al, 2009;Mansell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measured actual concentrations of BDE-209 in water were decreased relative to the nominal concentrations of the treatment groups (about 20% decrease; supplementary data Table S3). This could be due to BDE-209 sorption to tank, fish, and water particulates, or degradation during the exposure period (Zeilinger et al, 2009).…”
Section: Pb and Bde-209 Concentrations In Watermentioning
confidence: 99%
“…Previous environmental studies about steroid hormones mostly focused on estrogens [4][5][6][7] and a few studies on other steroids such as progestagens [8][9][10][11]. It is now well established that various natural and synthetic progestagens are widely used in humans and animals daily life for many reasons [12,13], and recent studies have shown the reproductive toxicity of progestagens to aquatic organisms at nanograms per liter levels [14][15][16][17][18][19]. Therefore, the presence of progestogens in the environment should deserve greater attention, and it is essential to develop sensitive and reliable analytical methods for determination of the broad number of progestagens in various environmental matrices in order to assess their environmental risks.…”
Section: Introductionmentioning
confidence: 99%